Consensus movements by groups of sperm whales. Issue 4 (24th August 2016) - Whitehead, Hal
Abstract: When animals live in cohesive groups they need to make consensus decisions about movements. As a very large‐scale example of communal movement, nomadic female sperm whales ( Physeter macrocephalus ) travel about 50 km per day as coherent groups of 10–50 animals spread over several km of ocean. From 543 h of data during which 3, 873 headings of small clusters of whales or individual whales were recorded, I quantified the heading behavior of groups foraging off the Galápagos Islands. The groups made both sudden and gradual turns. Using piecewise regression models, I estimate that sudden and gradual turns in heading both occurred at rates of 0.10/h. The mean change in heading was 69° for sudden turns and 84° for gradual turns. The mean duration of gradual turns was 1.3 h, so turns were often slow. Using the recorded headings within 30 min of each of 1, 798 focal headings, a regression of heading on time gave a mean rate of turn of the group and error of each focal heading about the mean heading. Absolute heading errors increased with absolute turn rate ( r S = 0.241; P = 0.0000), so turns were often messy. Thus sperm whales often make slow and messy—likely democratic—consensus decisions when groups change heading.